PP186 Telemonitoring With Pacemakers For Patients With Heart Failure. (2019) - Myles, Susan; Poole, Ruth Louise; Facey, Karen
Abstract : Introduction: Evidence supporting the use of pacemakers is well established. However, evidence about the optimal use of pacemaker telemonitoring for disease management in heart failure is not. Health Technology Wales (HTW) held a national adoption event to encourage implementation and best practice in use of pacemaker telemonitoring in the National Health Service (NHS) Wales to improve patient outcomes in heart failure. Methods: Multi-stakeholder national adoption workshop using a mixture of expert presentations, case studies and interdisciplinary group and panel discussions to agree key actions to understand the value and promote optimal use of pacemakers for remote disease monitoring in patients with heart failure in Wales. Results: The workshop was attended by forty-five senior professionals with an interest in improving care of patients with heart failure. Actions to progress included: providing a centralized Welsh system to support technical issues that arise with telemonitoring; considering interoperability with other NHS Wales systems; encouraging value-based procurement with collection of a core outcome set; agreeing implementation issues with both professionals and patients; audit to understand experience, resource use and outcomes; and sharing manufacturer evidence on the accuracy of telemanagement algorithms. It was suggested that these actions be progressed via an All-Wales multi-stakeholder approach, led by the Welsh Cardiac Network. Conclusions: Developing a more agile, lifecycle approach to technology appraisal is currently advocated; recalibrating the focus from technology assessment to technology management across the complete technology lifecycle. HTW will endeavour through regular adoption events to facilitate such a paradigm shift that aims to understand value and optimise use of evidence-based technologies.